A simple route to a novel acid-sensitive 20(S)-O-linked camptothecin norcantharidin acid ester derivative. Issue 2 (14th February 2018) - Zhao, Changkuo; Wang, Xianheng; Yang, Fuhong; Gao, Lei; Wang, Yuhe
Abstract : A facile synthetic method was developed for a novel acid-sensitive camptothecin norcantharidin acid ester derivative I . The total yield can reach 71%. This method provides several advantages, including high yield and simple working procedure for the synthesis of analogues. The new synthetic compound I has been shown to exhibit better solubility and similar activity against tumour cell lines.